COMBATING CORRUPTION AND PREVENTING CONFLICTS OF INTEREST (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the work being done in the Republic of Uzbekistan to combat corruption and prevent conflicts of interest. It states that corruption is a path leading to the destruction of society, that it is necessary to fight it without compromise in all its manifestations, and that conflicts of interest should not be allowed.